17d-3=9d+45

Simple and best practice solution for 17d-3=9d+45 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 17d-3=9d+45 equation:


Simplifying
17d + -3 = 9d + 45

Reorder the terms:
-3 + 17d = 9d + 45

Reorder the terms:
-3 + 17d = 45 + 9d

Solving
-3 + 17d = 45 + 9d

Solving for variable 'd'.

Move all terms containing d to the left, all other terms to the right.

Add '-9d' to each side of the equation.
-3 + 17d + -9d = 45 + 9d + -9d

Combine like terms: 17d + -9d = 8d
-3 + 8d = 45 + 9d + -9d

Combine like terms: 9d + -9d = 0
-3 + 8d = 45 + 0
-3 + 8d = 45

Add '3' to each side of the equation.
-3 + 3 + 8d = 45 + 3

Combine like terms: -3 + 3 = 0
0 + 8d = 45 + 3
8d = 45 + 3

Combine like terms: 45 + 3 = 48
8d = 48

Divide each side by '8'.
d = 6

Simplifying
d = 6

See similar equations:

| 2p+9=6p-27 | | 9t+10t=38 | | -c+2=-6c-13 | | 654/15 | | -2w+1=-7w+41 | | 5h=3x+150 | | -2f-6=-5f-3 | | 11d+5=3d-3 | | 7z-6=3z+4 | | -8k+4=-6k+20 | | 9j-4=5j+28 | | -6u+7=u+70 | | y/5=-20 | | 11u+1=6u-29 | | -x-4=-4x+2 | | -8g+7=-g+63 | | 70=6x-14 | | 7j-4=3j-28 | | 10e-4=4e-10 | | 2a+4=-3a-36 | | -2q+6=3q-24 | | 2x-1=-x-28 | | 6h-4=h-9 | | 9y-1=5y+15 | | 12+8=5d+57 | | 7(3g+8)/4=35 | | 8-32x+27x-3=0 | | 4(x-5)=-1.6 | | 12d+8=8d+16 | | 13=5c-9 | | 9e-7=28.1 | | 8(x-2)=26.4 |

Equations solver categories